Large-scale experimental investigation of a low-cost PVC 'sand-wich' (PVC-s) seismic isolation for developing countries. Issue 4 (November 2020) - Tsiavos, Anastasios; Sextos, Anastasios; Stavridis, Andreas; Dietz, Matt; Dihoru, Luiza; Alexander, Nicholas A.
This study presents a large-scale experimental investigation on the seismic performance of an innovative, low-cost seismic isolation system for developing countries. It is based on the beneficial effect of the encapsulation of sand grains between two PVC surfaces on the initiation of sliding and the dissipation of seismic energy between the surfaces. A three-times scaled-down, idealized, seismically isolated model of a prototype single-story structure located in Nepal is subjected to an ensemble of recorded earthquake ground motion excitations. The experimentally derived response of the seismically isolated structure is compared with the response of the corresponding fixed-base structure. This system is part of a wider hybrid design approach where the structure is designed to resist the seismic forces at the design acceleration level. The seismic isolation system sets an upper bound to the response of the structure for ground motion excitations exceeding the design level.